BASIC MODEL TO EXPLAIN THE COMPUTED TOMOGRAPHY USING ALGEBRAIC RECONSTRUCTION PROCESS - Chávez Ramírez, Edwin (2013)
Computed tomography (CT) is one of the major technological advances used in medicine to diagnose diseases, but it is also a technique used in other areas, such as eroespacial chemistry, radio astronomy, etc.. The goal of CT is to reconstruct the inside of an object without the need to open it, this process is known a nondestructive testing. To achieve this purpose, the TC uses suffering atenución X-rays to go through said object with said internal information of the object is reconstructed, this is an inverse problem. We got out of the theory and we focus on the practice showing concretely how the inside of an object using an algebraic method known as algebraic reconstruction for a specific event is reconstructed.